Efeitos de uma marca social na decisão de compra : um estudo experimental - Vieira, Fabricia de Sousa (Universidade de Fortaleza, 2017)
Made available in DSpace on 2019-03-30T00:21:53Z (GMT). No. of bitstreams: 0 Previous issue date: 2017-07-04 === In the last few decades, the consumer profile has changed, and those consumers have been more and more engaged and willing to search for ways to comply social, economic and environmental roles. In this context, the brands that invest in causes that have a positive impact on society, by engaging in actions that transform people¿s lives, have become more noteworthy and have also created meaningful debates. This dissertation work analyzed the influence of a Social Brand in the purchase decision making process of consumers. More specifically, it aimed at investigating if the Social Brand would influence positively the value noticed by the consumer, the justice judgement on the prices charged by such a brand, and his purchase decision making process in a context where the Social Brand presents higher prices than the competition. In order to find those answers, an experimental study was conducted with two groups of students, all women, from under graduation courses in business, marketing and advertisement of two different institutions. The results have shown that consumers perceived a higher value on the Social Brand offer and were willing to pay 10% more for its product, understanding that this price difference was fair, in a context where there were similar product options === Nas últimas décadas o perfil do consumidor tem mudado, e estes revelam-se cada vez mais engajados e dispostos a buscarem formas de aliar o papel social, econômico e ambiental. Nesse contexto, as marcas que investem em causas que impactam positivamente na sociedade, realizando ações sociais que transformam realidades de vida, vem ganhando importância e gerando debates significativos. Esta dissertação analisou a influência de uma Marca Social da decisão de compra dos consumidores. Mais especificamente, buscou-se investigar se a Marca Social influenciaria positivamente o valor percebido pelo consumidor, o julgamento da justiça no diferencial de preço cobrado por esta, e sua decisão de compra, em um contexto onde a Marca Social pratica um preço mais alto do que a concorrência. Para encontrar as respostas foi realizado um estudo experimental, com dois grupos de estudantes, mulheres, dos cursos de graduação em administração, marketing e publicidade e propaganda de duas instituições de ensino superior. Os resultados indicaram que os consumidores pesquisados perceberam um valor maior na oferta da Marca Social, mostrando-se dispostos a pagar 10% a mais pelo seu produto, julgando este diferencial de preço como justo, em um contexto onde havia outras opções de produtos semelhantes